2017
DOI: 10.1002/gepi.22055
|View full text |Cite
|
Sign up to set email alerts
|

Accommodating missingness in environmental measurements in gene‐environment interaction analysis

Abstract: For the prognosis of complex diseases, beyond the main effects of genetic (G) and environmental (E) factors, gene-environment (G-E) interactions also play an important role. Many approaches have been developed for detecting important G-E interactions, most of which assume that measurements are complete. In practical data analysis, missingness in E measurements are not uncommon, and failing to properly accommodate such missingness leads to biased estimation and false marker identification. In this study, we con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…It is appealing to conduct integrative G × E analysis to unravel the role that interaction effects play in multi-level omics integration studies and how additional strength that G × E interactions bring to integration. The missingness in environmental and clinical covariates can be efficiently accommodated by the existing approach [127]. Such an endeavor will motivate the development of novel variable selection methods for integrative G × E interactions.…”
Section: Discussionmentioning
confidence: 99%
“…It is appealing to conduct integrative G × E analysis to unravel the role that interaction effects play in multi-level omics integration studies and how additional strength that G × E interactions bring to integration. The missingness in environmental and clinical covariates can be efficiently accommodated by the existing approach [127]. Such an endeavor will motivate the development of novel variable selection methods for integrative G × E interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that tobacco smoking is responsible for 90% of lung cancer [25], and has been identified as a negative prognostic factor for lung adenocarcinoma [26]. In addition, these factors have also been considered in G–E interaction analysis [27].…”
Section: Datamentioning
confidence: 99%
“…In particular, the method in Bien et al () is also solved via penalized estimation. With the hierarchy and regularized estimation, the proposed approach has an analysis framework more coherent with that of the joint analysis (Liu et al, ; Wang, Xu, & Ma, ; Wu, Jiang, Ren, Cui, & Ma, , ; Zhao, Zhang, Clark, Maity, & Wu, ). This coherence facilitates methodological developments as well as biological interpretations.…”
Section: Introductionmentioning
confidence: 99%